Horizontal and Vertical FDI: a comparative analysis of technological determinants - Chiara Franco (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
The study analyzes the role played by technological determinants, using the approach of National System of Innovation (NSI), in enhancing or hampering Foreign Direct Investments (FDI) with different motivations, namely horizontal and vertical FDI. The empirical analysis is carried out using data relative to the final destination of sales of US foreign subsidiaries in 42 host countries grouped according to income criteria. A three step empirical strategy is employed: first, we estimate a benchmark model finding that technological determinants exert a greater in influence in high income countries especially for vertical FDI. Secondly, applying a dynamic panel data approach we take into account that agglomeration economies may play a role as well as other FDI determinants. Finally, we are able to further disentangle the destination of sales according to whether they are directed towards other foreign affiliates or to unaffiliated persons recognizing that they are affected by different determinants.
Keywords: F20; F23; O30; 330